Study on Deformation Characteristics of Loess Ultrahigh-Fill Slope Based on Large-Scale Undisturbed Soil Centrifugal Model Tests - Mei, Yuan; Zhou, Dong-bo; Hu, Chang-ming; Wang, Xue-yan; Zhang, Yuhang; Xiao, Nan; Shi, Wenyan (Frontiers in Earth Science, 2022)
Taking the loess high-fill project of Lv Liang airport in China as the research object, large-scale centrifugal tests were carried out to investigate the deformation characteristics of the collapsible loess ultrahigh-fill slope under natural moisture content and saturated state by using a joint model of undisturbed loess and remolded loess. The results show that the consolidation deformation of the collapsible loess ultrahigh-fill slope is the main factor causing its deformation. The post-construction deformation amount and deformation rate are large in the early stage, and the relationship between the post-construction deformation and thickness of filling body is linear. When the water content of soil increases due to infiltration, the consolidation of the filling body and the collapse of the undisturbed foundation loess will cause settlement and deformation of the slope. The slope may crack along the soft zone formed when the water infiltrates. When failure occurs, the sliding surface will pass through the collapsible soil layer. The contact surface between the collapsible loess layer and the adjacent soil layer is part of the sliding surface, and the contact surface with a relatively low strength will be damaged first. When the strength difference between adjacent soil layers is large, the upper soil layer on the slip surface shows a typical translational sliding mode. The slip surface is approximately arc-shaped, and there is a transition layer with a specific thickness between the slip surface and contact surface. The water content of the high-fill slope has a great influence on the post-construction settlement of the slope crest and slope stability. The post-construction settlement of the slope crest increases with the increase in the water content of the filling body, and the stability coefficient of the slope decreases with the increase in the water content of the filling body. In the saturated state, the sliding force of soil increases, the shear strength decreases, and the stability of high fill slope decreases. Therefore, it is necessary to strengthen the inspection of the rationality of drainage system design in slope construction to ensure slope safety.